Penggunaan Media Benda Konkret Dalama Upaya Meningkatkan Minat Belajar Matematika Siswa SD Negeri 6 Mas - Ni Luh Ketut Eka Juwitya Antari; I Ketut Sudarsana; Gusti Ayu Agung Riesa Mahendradhani (Sekolah Tinggi Agama Hindu Dharma Nusantara Jakarta, 2023)
Mathematics is one of the important lessons so that students can later apply it in solving problems in everyday life. Unfortunately mathematics is often regarded as a difficult and frightening subject. However, this is not very visible for students at SD Negeri 6 Mas. This is suspected because the teacher uses concrete media objects in the process of learning mathematics to increase students' interest in learning. Students seem happy and enthusiastic during learning activities. Interest in learning greatly determines the success of the teaching and learning process in the classroom. This study aims to: 1) describe the use of concrete object media in an effort to increase students' interest in learning mathematics, and 2) describe the impact of the use of concrete object media. The theory used to analyze this problem is the theory of classical conditioning and behavioristic theory. Methods of data collection using observation, interviews, and documentation. The collected data were analyzed using triangulation techniques. The results of the study show that: 1) the use of concrete object media in mathematics learning is applied to certain materials, most of the material in the lower class can use concrete object media as teaching media, and only a few materials in the high class can use concrete object media as teaching media; 2) the media of concrete objects has an impact on increasing students' interest in learning as indicated by the attitude of not getting bored easily, feeling happy and excited to take part in learning, enthusiastic and concentrating, so it is easy to remember what they have learned.